O mapeamento do fluxo de valor como ferramenta para melhoria no processo produtivo de um frigorífico na região oeste do Paraná - Jesus, Gabriel Cabral de (2014)
The reality Implies in think on different ways to save the market, Which ends driving the industry to use the techniques to help the management and optimization of processes and resources; Therefore, companies need to work on continuous improvement of processes and products looking for Reducing costs, and maximizing the bottom line. This paper is about the analysis of the production system from a food’s industry, which produces pork’s derivatives, located in western Paraná, through the Mapping Tool Value Stream. Has based on the theoretical framework of John Shook and Mike Rother Considering the MFV a simple tool that assists in the introduction and the use of lean thinking through the creation of the value’s identification. The practical tool Has Been Identified in the Toyota Production System, Which produce maps of value has been the routine. This way the MFV was presented as an improvement idea, making easy to identify the current map waste, coming up with the use of lean production tools that fits the future map. This is an exploratory research with qualitative approach in Which Were used techniques of observation, literature and documentary. Views Were Performed in the production of meat process in order to understand the steps of value creation and the variables that most have influenced in the process. This way was possible to know the process, mounting the MFV and suggesting lean tools that helps the production system.